Conflict Management Strategies : Improving Team Performance Through Collaboration and Communication (Human Resource Management Literature Study) - Mitha Virgina Rusady; Achmad Fauzi; Agus Triyan Syamsul Bachri; Micky Arnold Meyrlon Ballo; Eduardus Nuru (Dinasti International Journal of Education Management And Social Science, 2024)
This study looks at conflict management strategies that apply productive cooperation and communication to enhance team performance. As part of the literature analysis process, several conflict resolution strategies employed by work teams were evaluated to determine how they affected both individual and group performance. An assessment of these tactics' contribution to creating a peaceful and effective work environment was one of the research's goals. It is intended that this research will help determine the most effective approaches that not only deal with conflict in a positive way but also promote teamwork and collaboration. In order to improve work satisfaction, employee engagement, and overall organizational performance, useful advice will be made to assist organizations in implementing effective conflict management practices. Findings from the literature also highlight the importance of collaboration and effective communication in improving team performance. Therefore, conflict management strategies, collaboration, and good communication are considered key interacting factors in creating a productive, innovative, and harmonious work environment, which becomes crucial for team success in various organizational contexts.